‘Angry and heartbroken for the failure of the system’: A content and thematic analysis of viewer reactions to When They See Us - Henry, Taya D.; Clow, Kimberley A.; Zannella, Lesley (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2023)
As the number of wrongful conviction media productions released to the public increases, an understanding of their potential impact on viewers is prudent. One such production, When They See Us, depicts the wrongful conviction of five racialized youth, and we investigated the effect of watching this specific wrongful conviction media production on a subset of Reddit users’ online conversations about wrongful convictions and the criminal justice system in general. Following an inductive content analysis of Reddit comments shared to r/WhenTheySeeUs (N = 461), seven coding categories were observed. The ‘Wrongful Conviction Relevant’ coding category was the third most frequently occurring, representing 28% of total comments. Additionally, after conducting a deeper thematic analysis of the ‘Wrongful Conviction Relevant’ comments, the following themes and subthemes were identified: Risk Factors (Individual Characteristics and System Factors), Exoneration and Beyond (Impacts on Exonerees and Changes to System), and the Innocence Movement (Unmet System Expectations and Public Awareness). Users’ ‘Wrongful Conviction Relevant’ comments were situated within the academic literature investigating wrongful conviction correlates, outcomes, and preventative measures, and discussed in relation to viewer reactions to other wrongful conviction media productions.